2014
DOI: 10.1371/journal.pone.0105492
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the TNFA and IL6 Genes Represent Risk Factors for Autoimmune Thyroid Disease

Abstract: BackgroundAutoimmune thyroid disease (AITD) comprises diseases including Hashimoto's thyroiditis and Graves' disease, both characterized by reactivity to autoantigens causing, respectively, inflammatory destruction and autoimmune stimulation of the thyroid-stimulating hormone receptor. AITD is the most common thyroid disease and the leading form of autoimmune disease in women. Cytokines are key regulators of the immune and inflammatory responses; therefore, genetic variants at cytokine-encoding genes are poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 55 publications
3
18
0
Order By: Relevance
“…For example, vitamin D takes part in the regulation of cytokines, such as interleukin (IL)-1, IL-6, IL-17, TNF-α, and leptin, which has been found to play an important role in AITD. 1 4 , 35 – 37 Further research is required in this field. Would supplementation of vitamin D be beneficial to AITD patients, given that lower serum vitamin D level is associated with higher risk of this disease?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, vitamin D takes part in the regulation of cytokines, such as interleukin (IL)-1, IL-6, IL-17, TNF-α, and leptin, which has been found to play an important role in AITD. 1 4 , 35 – 37 Further research is required in this field. Would supplementation of vitamin D be beneficial to AITD patients, given that lower serum vitamin D level is associated with higher risk of this disease?…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune thyroid diseases (AITD) are the most common organ specific autoimmune disorder. 1 3 Graves’ disease (GD) and Hashimoto's thyroiditis (HT) are the 2 main clinical presentations of AITD and are both characterized by lymphocytic infiltration of the thyroid parenchyma. The clinical hallmarks of GD and HT are thyrotoxicosis and hypothyroidism, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with type 2 diabetes, rs1800795 SNP of the IL-6 gene is significantly related to increased risk of cardiovascular disease [15]. In addition, rs1800795 SNP of the IL-6 gene is related with autoimmune diseases such as systemic lupus erythematosus [16], systemic sclerosis [17], and autoimmune thyroid disease [18]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that SNPs of IL-6 may influence the development of cardiovascular disease, 28 cancer, 29 30 fractures 31 and autoimmune diseases. [32][33][34] In contrast, there is less available research regarding TIE2 gene polymorphisms, except for a study on the relationship between rs638203/rs639225 and vascular malformations. 35 In this study, we investigated the effect of genetic polymorphisms of IL-6 and TIE2 on the baseline peritoneal transport property.…”
Section: Discussionmentioning
confidence: 99%